Synthesis of mass exchange network for batch process systems. part 1 : calculation of utility targets - Foo, Chwan Yee; Zainuddin Abdul Manan; Rosli Mohd. Yunus; Ramlan Abd. Aziz, 1958-; Regional Symposium on Chemical Engineering (2002 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2002)
50